2018
DOI: 10.3390/met8070501
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Mechanical Properties of Hot-Forged 6082 Suspension Parts via Rapid IR Heat Treatment

Abstract: Post-forging heat treatment is often necessary to achieve the mechanical properties required for aluminum alloy forged parts. In this study, hot-forged 6082 suspension parts are used to study the effect of rapid infrared (IR) heat treatment. The insoluble particles present in the matrix after the solutionizing process are observed. Experimental results show that using rapid IR heat treatment leads to superior solutionizing, and thus a larger critical onset strain in serrated tensile flow. The rapid IR heat tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Figure 2 shows photographs of the IR heating furnace. The heating rate of the IR heating furnace has been published in our previous research [7]. The heat treatment was performed in an infrared (IR) heating furnace and a resistance heating (RH) furnace (RH, CM30S, CHENG SANG, Changhua, Republic of China (Taiwan)), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows photographs of the IR heating furnace. The heating rate of the IR heating furnace has been published in our previous research [7]. The heat treatment was performed in an infrared (IR) heating furnace and a resistance heating (RH) furnace (RH, CM30S, CHENG SANG, Changhua, Republic of China (Taiwan)), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 shows photographs of the IR heating furnace. The heating rate of the IR heating furnace has been published in our previous research [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al [6] have experimentally analyzed the influence of technological parameters on the mechanical properties of the AA6082 Al alloy and revealed the strengthening mechanism of the Al alloy by observing and analyzing the distribution of precipitated phases. By employing rapid infrared thermal processing, Chang et al [7] have found a large initial critical strain on the 6082 Al alloy during rapid solution treatment and a more significant precipitation strengthening effect. Thus, the mechanical properties of materials were strengthened.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting mechanical, durability, and corrosion properties of the forgings are the result of interaction of the initial structure, the hot deformation parameters, solution annealing, and artificial aging. Therefore, these relatively complicated connections have been the subject of several research works (see References [13][14][15][16]).…”
Section: Introductionmentioning
confidence: 99%